Development and Dissemination of Integrated Crop Management (ICM) Technologies for Management of Biotic and Abiotic Stresses affecting Common bean in PABRA - Abang, Mathew M.; Chirwa, Rowland; Rubyogo, Jean-Claude; Mukankusi, Clare Mugisha (Pan-Africa Bean Research Alliance, 2012)
The common bean is sensitive to many biotic and abiotic constraints. To enhance farm productivity, farmers need to have access to and use bean production practices that combine seed of improved varieties as well as integrated soil fertility management (ISFM) and integrated pest and disease management (IPDM) technologies. This poster describes efforts and achievements by the Pan Africa Bean Research Alliance (PABRA) in the development and delivery of IPDM and ISFM technologies to improve bean productivity across sub-Saharan Africa. Over 50 crop management technologies, IPDM (36) and ISFM (23) have been tested on-station and on farm in different PABRA countries, including: pest/disease tolerant varieties, staking techniques for climbing beans, botanical pesticides for storage pests, intercropping, varietal mixtures, pesticide application, organic and inorganic fertilizers, tithonia, manure amendments, N-P-K application, and integrated management options for major diseases, bean stem maggot and bean bruchids. A two-pronged approach was used to increase access to ISFM/IPDM technologies which involved; i) a deliberate promotion and delivery of improved varieties and ICM technologies as a single package, and ii) the harnessing of enabling policies (including input support systems) to deliver ICM technologies to bean farmers. The combined use of new stress tolerant varieties and improved crop management practices led to yield increases of 65% (Ethiopia) to 400% (DR Congo). The two-pronged approach led to the delivery of ICM technologies to 4.9 million farmers during 2009 – 2011. In countries where the approach was either not